Effect of heat treatment on the physical stability, interfacial composition and protein-lipid co-oxidation of whey protein isolate-stabilised O/W emulsions - Chen, Jiaxin; He, Junjie; Zhao, Zihan; Li, Xin; Tang, Jie; Liu, Qian; Wang, Hui (Food research international, 2023)
[Display omitted] •Heat treatment decreased the physical stability of O/W emulsions.•Increasing temperature alter the structure of adsorbed and unadsorbed proteins.•Interfacial composition degraded with increasing temperature.•Heat treatment retarded the protein-lipid co-oxidation of O/W emulsions. This work aimed to investigate the effects of heat treatments at different temperatures (60, 70 and 90 °C, expressed as HT-60, HT-70 and HT-90) on interfacial composition and protein-lipid co-oxidation in whey protein isolate (WPI)-stabilised O/W emulsions during storage. Compared with control group, all heated emulsions exhibited weaker physical stability over 10 days of storage, which verified by the increased droplet size, as well as decreased adsorbed protein levels and absolute ζ-potential values. Moreover, proteins recovered from the HT-90 emulsion showed the highest fluorescence intensity and red-shift of the maximum emission wavelength, indicating partial unfolding of the protein structure. Meanwhile, severe changes in protein structure were also observed in the HT-70 and HT-90 emulsions, which clearly verified by the degradation of bovine serum albumin, α-lactalbumin and β-lactoglobulin. Furthermore, HT-70 and HT-90 emulsions showed lower levels of lipid hydroperoxides and thiobarbituric acid reactive substances. In contrast, the recovered proteins were subject to severe oxidative stress as indicated by carbonyl and N’-formyl-L-kynurenine. Hierarchical cluster and correlation analysis implied that the process of protein-lipid co-oxidation is inevitable, but it can be retarded by heat treatment. Our results clearly revealed the relevance among heat treatment, interfacial adsorption property, and the protein-lipid co-oxidation of O/W emulsions.